Pemberian scaffolding dalam pemecahan masalah matematis siswa SMP - Alfi Syahraini; Nanang Priatna; Suhendra Suhendra (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to observe students' systematic problem solving by applying scaffolding. Providing a framework plays an important role for students who struggle to solve problems in the system of linear equations of two variables. The research subjects were Jambi Junior High School VIII grade students as many as two students. The research method used is descriptive qualitative method applied in the research process with data collected through Polya's problem solving description test two questions with unstructured interviews. Two students who solve problems in the form of descriptions begin to plan solutions to problems that are analyzed in general. So, the framework that can be given consists of description, structuring, and validation. Errors in problem solving can be addressed by observing the understanding of the problem, planning the solution, implementing the solution plan, and checking back.